2015
DOI: 10.15517/rbt.v63i2.15240
|View full text |Cite
|
Sign up to set email alerts
|

Ostrácodos no-marinos de lagos en el altiplano este-centro de México

Abstract: Abstract:The ostracode fauna of the neartic-neotropical transitional zone has remained poorly known until this study. Ten ostracode species inhabit ten highland lakes (five maar lakes (phreatic/phreato-magmatic explosion origin), one volcanic-tectonic lake, three natural dams and one man-made dam) in East-central Mexico. Surface sediments from the deepest part and the littoral zone from all studied lakes were collected. Environmental variables (pH, temperature, dissolved oxygen, conductivity, TDS) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…This approach is actually the opposite one to "Sampling Effect Hypothesis" (Hıll et al 1994). Similar results were also reported previously (e.g., see Külköylüoğlu (2004), Nagorskaya & Keyser (2005), Pıerı et al (2009), Akdemİr & Külköylüoğlu (2011), Yavuzatmaca et al (2015) and Yavuzatmaca et al (2017)). On the other hand, Külköylüoğlu et al (2016) emphasized the significant relationships (p < 0.01) between the frequency of occurrence and number of sampled sites in some elevational ranges.…”
Section: Discussionsupporting
confidence: 86%
“…This approach is actually the opposite one to "Sampling Effect Hypothesis" (Hıll et al 1994). Similar results were also reported previously (e.g., see Külköylüoğlu (2004), Nagorskaya & Keyser (2005), Pıerı et al (2009), Akdemİr & Külköylüoğlu (2011), Yavuzatmaca et al (2015) and Yavuzatmaca et al (2017)). On the other hand, Külköylüoğlu et al (2016) emphasized the significant relationships (p < 0.01) between the frequency of occurrence and number of sampled sites in some elevational ranges.…”
Section: Discussionsupporting
confidence: 86%
“…As previously stated (e.g., KÜlkÖylÜoğlu et al 2012c, Yavuzatmaca et al 2017a, the high species diversity was reported in the mid-elevational interval in the present study (Table 2). Whereas the finding of high diversity at low (e.g., Pèrez et al 2015 and high (e.g., KÜlkÖylÜoğlu et al 2012aKÜlkÖylÜoğlu et al , 2016 elevational intervals are also available in the literature. The difference between the present study and previous ones is the difference in the elevation ranges used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is no any studies dealing the number or quality of eggs of species in low and high DO concentration and so the proposal of Ranta (1979) may be acceptable until otherwise stated. In addition, minimum and maximum values of ambient air temperature (12-40.20 ºC) (Horne 2007; the current study), calcium (5.25-80.80 mg/L) (Higuti et al 2009a;Pérez et al 2015) and magnesium (2.30-100.80 mg/L) (Holmes 1997;Pérez et al 2015) contents of water bodies where species collected.…”
Section: Discussionmentioning
confidence: 54%